Hepatitis B vaccine coverage in health care students: a cross-sectional study in Vietnam. - Ly Trieu Vo; Dung Quoc Phan; Huy Gia Tran; Lam Thi Phuong Nguyen; Araba Gyan; Han Thi Ngoc Nguyen; Giao Huynh (PLoS ONE)
Hepatitis B virus (HBV) remains a significant global health concern, with healthcare students being at elevated risk of infection during their internships in healthcare settings. This study aimed to determine the percentage of healthcare students vaccinated against hepatitis B and the factors associated with vaccination status. A cross-sectional study was conducted among healthcare students at the University of Medicine and Pharmacy at Ho Chi Minh City in Vietnam between February and May 2023 using a self-reported questionnaire. Participants were selected through stratified and random sampling. A multivariable analysis logistic regression was performed to determine the association between several factors with vaccination status. A total of 225 participants took part in the study. We found that 89.8% of the participants had received at least one dose of the HBV vaccine, while 63.3% had completed the entire vaccine schedule. Students with sufficient knowledge of HBV were 2.68 times more likely to be vaccinated (p <  0.05), while those practicing effective HBV prevention had 8.79 times higher vaccination rates (p <  0.001) compared to others. The rate of HBV vaccination among healthcare students remains suboptimal. Targeted health education that addresses knowledge gaps, enhances motivation, tackles vaccination barriers, and emphasizes preventive measures before internships could substantially improve vaccination coverage in this group.